Association between rs4673 (C/T) and rs13306294 (A/G) haplotypes of NAD(P)H oxidase p22phox gene and severity of stenosis in coronary arteries - Najafi, Mohammad; Alipoor, Behnam; Shabani, Mohammad; Amirfarhangi, Abdollah; Ghasemi, Hassan (Gene, 2012)
Phagocytic NADH/NADPH oxidase is an important enzyme producing reactive oxygen species within subendothelial space of vessels. Findings have shown that p22phox subunit is an essential element related to the enzyme activity. Since some p22phox polymorphisms are thought to have functional roles in the enzyme thus, we studied the association between rs4673 (C242T) and rs13306294 (A/G) haplotypes and the severity of stenosis in coronary arteries. One hundred eighty-two subjects undergoing coronary angiography were recruited on the base of study design. Patients (n=114) had at least a stenosed coronary artery (>50% stenosis) and subdivided into three subgroups; SVD (n=28), 2VD (n=31) and 3VD (n=55) while controls (n=68) had the normal coronary arteries (<5% stenosis). The direct haplotyping technique of SNPs was performed using ARMS–RFLP–PCR method. Furthermore, alphabet-based tools predicted the changes of secondary structure at the rs4673 position. All haplotypes being proposed theoretically were found in the study population. The distribution of two-allele haplotypes had no significant difference between patients and controls (P=0.1). Although the rs4673 allele frequency was not significant between the groups (P>0.5), chi square test and multinomial regression analysis showed an observed high risk for rs13306294 A allele among patients. The bioinformatics tools predicted that the p22phox secondary structure is not changed due to the substitution of Tyr→His at the rs4673 position. We concluded that the polymorphisms have no allele linkage on the chromosome. In addition, the rs13306294 A allele is a potential factor of stenosis of coronary arteries that increases susceptibility for the extent of disease. ► The first study on direct haplotyping of SNPs. ► The first study in evaluation of rs13306294 in CAD patients. ► Use of bioinformatics tools for study of rs4673 substitution in secondary structure.